EMPLOYEE PERFORMANCE ANALYSIS THROUGH LEADERSHIP STYLE, MOTIVATION & WORK DISCIPLINE (AT WAROENG CHARITY MANADO) - Turangan, Reynold Briando; Pangemanan, Sifrid S.; Tielung, Maria V. J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Employee Performances are become important thing these days. Employee performance is assessed in terms of quality and quantity based on labor standards specified by the organization. Good performance is the optimal performance such as the appropriate performance standards of an organization and support achievement of organizational goals. There are many factors which give effect and influence in creating such a high employee performance. The purpose of this research is to know the effect of Leadership Style, Motivation and Work Discipline towards employee performance developed in Qualitative Method. This research used Qualitative Method , Descriptive Analysis to give a detail explanation about employee performance of Waroeng Charity based on the leadership style, motivation and work discipline as the factors which giving a influence to create a high or low employee performances. To ensure the accuracy of the analysis, this research uses in-depth interview until we get the saturation. The result of this research discovered that three factors are the main consideration for both employee and leader. The leadership style isn’t suit enough with the employees, while the motivation & work discipline of the employee is really low. This means Waroeng Charity should reconsider to change the leadership style and focus improving the motivation and discipline by creating training and development. Keywords: employee performances, leadership style, motivation, work discipline